2021
DOI: 10.1111/gbb.12725
|View full text |Cite
|
Sign up to set email alerts
|

Generation and basic characterization of a gene‐trap knockout mouse model of Scn2a with a substantial reduction of voltage‐gated sodium channel Nav1.2 expression

Abstract: Large‐scale genetic studies revealed SCN2A as one of the most frequently mutated genes in patients with neurodevelopmental disorders. SCN2A encodes for the voltage‐gated sodium channel isoform 1.2 (Nav1.2) expressed in the neurons of the central nervous system. Homozygous knockout (null) of Scn2a in mice is perinatal lethal, whereas heterozygous knockout of Scn2a (Scn2a+/−) results in mild behavior abnormalities. The Nav1.2 expression level in Scn2a+/− mice is reported to be around 50–60% of the wild‐type (WT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 78 publications
(126 reference statements)
4
23
0
Order By: Relevance
“…We found that heterozygous (HET) Scn2a WT/gt mice have ~60% of WT Na V 1.2 protein level in homogenate from CPu tissues, whereas HOM Scn2a gt/gt mice have a much lower level at ~32% ( Figure S1C ). This result is largely consistent with our initial characterization of this mouse model using whole-brain homogenates ( Eaton et al, 2021 ).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…We found that heterozygous (HET) Scn2a WT/gt mice have ~60% of WT Na V 1.2 protein level in homogenate from CPu tissues, whereas HOM Scn2a gt/gt mice have a much lower level at ~32% ( Figure S1C ). This result is largely consistent with our initial characterization of this mouse model using whole-brain homogenates ( Eaton et al, 2021 ).…”
Section: Resultssupporting
confidence: 90%
“…To understand the consequences of severe Na V 1.2 deficiency in neurons, we utilized a Na V 1.2-deficient mouse model generated using a gene trap (gt) approach ( Eaton et al, 2021 ). Homozygous (HOM) Scn2a gt/gt mice can survive to adulthood and have a substantial reduction of Na V 1.2 expression (~25% of the wild-type [WT] level) ( Eaton et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations